Budaya Organisasi Pembelajaran sebagai Moderator Hubungan antara Core Self-Evaluation dengan Kreativitas Karyawan: Organizational Learning Culture as a Moderator of the Relationship between Core Self-Evaluation and Employee Creativity - Prita Adwi Minandarin Shamara; Arum Etikariena (Universitas Negeri Surabaya, 2021)
The aim of this research was to determine whether organizational learning culture plays a role as a moderator in the relationship between core self-evaluation and employee creativity. Data were gathered from three variety of industry in Indonesia, such as the state-owned bank industry, broadcast industry, and technology information industry, with N = 179 (52% woman, average age 22-30 years, average unmarried status, and S1 educational background) using cross sectional study. The analysis method for this study was a simple moderation technique from Hayes) and Harman’s single factor test technique for testing common method bias. The result of study showed that there were no significant interaction effect between core self-evaluation and organizational learning culture towards employee creativity. This result supports previous research which found that organizational learning culture had no significant role in strengthening the relationship between domain expertise, creative personality, and employee creativity. Key words: Core self-evaluation, creativity, organizational learning culture Abstrak: Penelitian ini bertujuan untuk mengetahui apakah budaya organisasi pembelajaran dapat menjadi moderator pada hubungan langsung antara core self-evaluation dengan kreativitas karyawan. Data diambil dari tiga jenis industri di Indonesia, seperti industri bank BUMN, industri penyiaran, dan industri teknologi dan informasi dengan N = 179 (52% perempuan; rata-rata usia 22-30 tahun, rata-rata berstatus lajang, dengan latar belakang pendidikan terakhir S1) melalui teknik penelitian cross sectional study. Proses analisis data menggunakan analisis moderasi sederhana dari Hayes dan teknik Harman’s single factor test untuk menguji common method bias. Hasil dari penelitian ini menunjukkan bahwa tidak adanya efek interaksi yang signifikan antara core self-evaluation dan budaya organisasi pembelajaran terhadap kreativitas karyawan. Hasil ini mendukung penelitian sebelumnya yang menyatakan bahwa budaya organisasi pembelajaran tidak memiliki peran secara signifikan dalam menguatkan hubungan antara domain expertise, creative personality dengan kreativitas karyawan.